10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
INTRODUCTION: Agility is a fundamental motor skill in dance performance, enabling rapid and efficient changes of direction in response to choreographic, musical, and environmental demands. Despite its importance, there is no standardized, validated field-based agility test specifically established for dancers. This study aimed to evaluate the test-retest reliability, construct validity, and discriminative validity of the Hexagon Test in dancers. METHODS: This cross-sectional test-retest study included 32 trained dancers (12 hip-hop, 10 ballet, and 10 Latin dancers; 20 females, 12 males; age: 23.0 ± 3.9 years) and 42 sedentary individuals (24 females, 18 males; age: 22.9 ± 2.9 years). Agility was assessed using the Hexagon Test (time in seconds) and the Edgren Side Step Test (ESST; distance in meters). All participants completed 2 testing sessions separated by 1 week under standardized conditions. Test-retest reliability was analyzed using intraclass correlation coefficients (ICC), standard error of measurement (SEM), and minimal detectable change (MDC). Construct validity was examined using Pearson correlation analysis between the Hexagon Test and ESST. Discriminative validity was evaluated using receiver operating characteristic (ROC) curve analysis. RESULTS: The Hexagon Test demonstrated excellent test-retest reliability (ICC = 0.96; 95% CI: 0.93-0.97). A strong negative correlation with the ESST (r = -0.72, P < .001) supported construct validity. ROC analysis revealed excellent discriminative validity, with an area under the curve of 0.91 (95% CI: 0.84-0.97), indicating a 91% probability of correctly distinguishing dancers from sedentary individuals. CONCLUSION: The Hexagon Test is a reliable and valid field-based tool for assessing agility in dancers. Its strong psychometric properties and practical feasibility support its use in dance performance screening and return-to-dance settings.